The overlapping region in right hippocampus accounting for the link between trait anxiety and procrastination. (September 2020) - Zhang, Rong; Chen, Zhiyi; Xu, Ting; Zhang, Libin; Feng, Tingyong
Abstract: Procrastination refers as putting off an intended course of action voluntarily despite expecting to be worse off for the delay, ubiquitously causing troubles across life domains. Prior studies revealed the positive correlation between trait anxiety and procrastination. However, little was known about the neural substrates responsible for the relation between trait anxiety and procrastination. To address this issue, the current study explored the neural basis underlying how trait anxiety linked to procrastination using the voxel-based morphometry (VBM) method across two independent samples. In line with previous studies, the behavioral result confirmed that trait anxiety was positively correlated with procrastination (sample 1). The VBM analyses showed that trait anxiety and procrastination shared the common neural underpinnings in the right hippocampus (sample 1). To verify the reliability of results, the overlapping region in the right hippocampus was defined as a region of interest (ROI) to extract the GM volumes of this area in sample 2. Furthermore, the mediation analysis showed that the GM volumes in the overlapping region played a mediating role in the relationship between trait anxiety and procrastination (sample 2). These results suggested the shared anatomical structure in the right hippocampus, a region implicated in episodic prospection, could be responsible for how trait anxiety related to procrastination. Taken together, present findings yielded insights into the role of episodic prospection accounting for the relationship between trait anxiety and procrastination from a neural basis perspective. Highlights: Individuals with higher trait anxiety were correlated with more procrastination. The right hippocampus was the shared neuroanatomical structure of trait anxiety and procrastination. The gray matter volumes in right hippocampus partially mediated the relation between trait anxiety and procrastination.